Modeling Battery Connections in the Electronic Lab - K. V. Dobrego; Yu. V. Bladyko (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика)
The paper deals with the modeling of the processes of charge-discharge of battery assemblies taking into account their degradation. The results of simulating the cyclic operation of battery assemblies in the Electronics Workbench electronic laboratory are presented, possible schemes of inclusion are given, and options for re-switching batteries during operation are considered as well as connecting additional elements to extend the life of the connection. The simulation took into account the presence of one defective battery in the assembly. The operation of the assembly with a defective battery and a reference battery was compared. As a result of the analysis of parallel-serial and serial-parallel battery connections, the first one is considered preferable. For an assembly with a parallel-serial connection, the time parameters of operation remained almost unchanged, but the differences in the voltages of the defective and other batteries changed more than twice as compared with a serial-parallel connection. The changes in charge, voltage and current of assemblies with a degraded battery and a reference battery are analyzed. Timing diagrams are shown for batteries connected in parallel and in series with defective batteries. Power losses in a defective battery are reduced by choosing a parallel-series assembly, while switching a connection from a serial-parallel connection to a parallel-series one does not lead to compensation for the degradation of battery parameters. Changing the switching time intervals in a wide range does not contribute to increasing the capacity of a defective battery. Degradation of battery parameters leads to sharper surges in voltage, charge and current. The additional power recharge of the defective battery maintains the performance of the entire assembly. Recharge can be performed by connecting in parallel a defective additional battery or a capacitor, which is equivalent to replacing a degraded battery with a new one.